Sky brightness during twilight : within the concept of physics and astronomical consideration / Nur Adyanie Mohamad - Mohamad, Nur Adyanie (2010)
Sky brightness during twilight is one of the interesting area that can be discover by some scientist and also for those people who love to discover about the nature of the universe and atmosphere. This study was done since a long time ago and it keeps continuing from time to time. As it was did in so many ways to see the differences and what are the things that related to this field, this project was done to discover and analyze what are the concept of physics and also its astronomical consideration that can be study especially during twilight. Most people know that during twilight the changes of the sky colour are extremely can be seen during that time and it can be divided into two variations of twilight which are evening twilight and morning twilight. So from this atmosphere, the condition of the sky brightness can be discovering easily by using Sky Quality Meter (SQM) equipment. From the data that was transferred into the computer, graph of the mag/arcsec2 versus the degree can be come out and also the luminance of twilight can be calculated from it. Here, the analysis of the sky brightness and its condition can be seen from the analysis of data. After all the experiment was successfully done, the objectives of the project was successfully achieved where the relationship between the concept of physics and it astronomical concept are can be seen it related to each other.